A fully reconfigurable waveguide Bragg grating for programmable photonic signal processing - Weifeng Zhang (Nature Portfolio, 2018)
Bragg gratings are versatile elements used to perform spectral filtering in optical circuits. Here, the authors develop a scalable, reconfigurable grating device which can be electrically tuned to actively change its behaviour and control of optical pathways, for use in photonic signal processing.